Bacterial status and pollution level in the water of Gulshan Lake, Dhaka (Bangladesh Journal of Zoology, 2013)
Water samples were collected from four selected sites of the Gulshan lake during four different seasons. Four different media were used to study the aerobic heterotrophic, enteric and related bacterial abundance. Aerobic heterotrophic bacterial abundance ranged between 1×106 and 9×106 cfu/100 ml, while enteric and related bacterial abundance in SS agar, MacConkey agar and Cetrimide agar media ranged between 1×103 and 3×105 cfu/100 ml, between 1×104 and 1×107, and between 1×100 and 1.4×103 cfu/100 ml, respectively. Among 40 bacterial isolates 14 were selected out of which seven were Gram-positive and seven were Gramnegative. Among Gram-positive isolates, six were rod-shaped spore former belonging to Bacillus and Lactobacillus, while another one was coccoid in shape and under the genus Planococcus. Out of seven Gram-negative isolates, two were the members of Pseudomonas, remaining five were Morganella, Neisseria, Escherichia, Aeromonas and Enterobacter. Inorganic nutrients like NH4+-N, NO3+-N, NO2+-N and PO4+ values were found to be satisfactory from pollution point of view. The presence of different bacterial isolates indicate that the Gulshan lake water was polluted with chemical and bacterial pollutants. DOI: http://dx.doi.org/10.3329/bjz.v40i2.14309 Bangladesh J. Zool. 40(2): 165-173, 2012